Efektivitas Self-Talk Terhadap Pengelolaan Kesehatan Mental di Tengah Pandemi COVID-19 - Hidayatullah, Rizky Maulana; Al Alufi, Faizatun Nissa (PSYCOMEDIA : Jurnal Psikologi, 2021)
This study aims to test the effectiveness of self-talk to overcome psychological disorders in the covid 19 pandemic. The hypothesis of this research is that there is an effect of self-talk to overcome psychological disorders in the covid 19 pandemic. This research method is a quasi-experimental type of one group pre-test and post-test design. The number of subjects are 20 subjects who experienced psychological disorders. The research instrument to screen for psychological disorders uses the Self Reporting Questionnaire (SRQ). Data analysis uses t test to test psychological disorders before and after the intervention. The results of the t-test analysis showes the t-value = 6.159 while the p-value is 0.000 (p<0.05), it means that there is a significant influence between pre-test and post-test data on research subjects, it means that there is a positive effect of self-talk in overcoming psychological disorders.